Examining the Psychometric Properties of the Iranian Version of the Covid-19 Job Burnout Scale(COVID-19-BS) - M Sharifi; F Bazarganipour; SAV Taqvi; A Khosravi; S Ebrahimi; A Montazeri; SH Amirjani; N Hosseini (Armaghane Danesh Bimonthly Journal, 2022)
Background & aim: Although tools for measuring job burnout have been psychometrically tested in Iran, it seems crucial to have an instrument that can be used by the general society. The Covid-19 burnout scale (COVID-19-BS) is the only tool available to assess the burnout following Covid-19 in the general population. Therefore, the purpose of the present study was to determine and examine the psychometric properties of the Iranian version of the Covid-19 Burnout Scale (COVID-19-BS).